2023
DOI: 10.1038/s41396-023-01482-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically diverse microorganisms mediate methylmercury formation under nitrate-reducing conditions in a dynamic hydroelectric reservoir

Abstract: Brownlee Reservoir is a mercury (Hg)-impaired hydroelectric reservoir that exhibits dynamic hydrological and geochemical conditions and is located within the Hells Canyon Complex in Idaho, USA. Methylmercury (MeHg) contamination in fish is a concern in the reservoir. While MeHg production has historically been attributed to sulfate-reducing bacteria and methanogenic archaea, microorganisms carrying the hgcA gene are taxonomically and metabolically diverse and the major biogeochemical cycles driving mercury (Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 93 publications
1
1
0
Order By: Relevance
“…The native function of hgcAB remains unknown (Parks et al, 2013), but its widespread presence across various taxonomic and functional groups suggests that this gene pair must have conferred a competitive advantage to microorganisms at some point. The potential co‐regulation between Hg methylation and arsenic detoxification has been recently proposed (Gionfriddo et al, 2023), and co‐occurrence of hgcA and arsenic detoxification genes in MAGs has also been noted in other studies (Lin et al, 2021; McDaniel et al, 2020; Peterson, Poulin, et al, 2023; Zhang et al, 2023; Zheng et al, 2022), a trend similarly identified in our study. It is plausible that the absence of specific drivers for the structure of Hg‐methylating communities is due to the potential loss of the native function of hgcAB .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The native function of hgcAB remains unknown (Parks et al, 2013), but its widespread presence across various taxonomic and functional groups suggests that this gene pair must have conferred a competitive advantage to microorganisms at some point. The potential co‐regulation between Hg methylation and arsenic detoxification has been recently proposed (Gionfriddo et al, 2023), and co‐occurrence of hgcA and arsenic detoxification genes in MAGs has also been noted in other studies (Lin et al, 2021; McDaniel et al, 2020; Peterson, Poulin, et al, 2023; Zhang et al, 2023; Zheng et al, 2022), a trend similarly identified in our study. It is plausible that the absence of specific drivers for the structure of Hg‐methylating communities is due to the potential loss of the native function of hgcAB .…”
Section: Discussionsupporting
confidence: 90%
“…The use of metagenome‐assembled genomes (MAGs) is highly pertinent for studying Hg methylators, as they can reveal microbial diversity (Baker et al, 2021) and inferring the metabolic capacities of microorganisms (Vavourakis et al, 2018). Recent studies recovered hgcA ‐containing MAGs from diverse environments, including lakes (Jones et al, 2019; McDaniel et al, 2020; Peterson et al, 2020), ocean (Capo et al, 2022; Langwig et al, 2022; Lin et al, 2021), mangroves (Peterson, Krabbenhoft, et al, 2023; Zhang et al, 2023), a reservoir (Peterson, Poulin, et al, 2023), contaminated sites (Vigneron et al, 2021; Zheng et al, 2022) and composting sludge (Liu et al, 2022). Two of these studies also mined for hgcA in publicly available MAGs retrieved from diverse environments, encompassing the aforementioned list but also including permafrost (McDaniel et al, 2020; Zhang et al, 2023), wetlands, estuaries, subsurface, hydrothermal vents, endosymbionts, engineered ecosystems and hot springs (McDaniel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%